Management of shooting sports coaching in Perbakin Cirebon City - Pini, Irma De; Khodari, Rahmad (Universitas Tanjungpura, 2022)
This study aims to analyze the implementation of management functions in shooting sports coaching in PERBAKIN Cirebon City. The research uses a qualitative descriptive approach with data collection techniques in the form of in-depth interviews, observations, and documentation of administrators, coaches, and athletes. The analysis is based on the four main functions of management—Planning, Organizing, Actuating, and Controlling—which are examined through seven management elements (7M): Man, Money, Material Machine, Method, Market, and Minute. The results of the study show that all four management functions have been carried out, although there are still technical and systematic shortcomings. At the planning stage, there is active stakeholder participation, including in the recruitment of athletes and the management of the budget from KONI, sponsors, and member dues. The organization is carried out formally, but it has not been supported by administrative digitization. At the implementation stage, the trainer has adjusted the training program personally, but it has not been documented in writing. Supervision is carried out by internal management and KONI, but it is still informal and has not used measurable performance indicators. This study concludes that the athlete coaching management system at PERBAKIN Cirebon City has been running well, but it still needs improvements in the aspects of documentation, digitization of organization, and indicator-based monitoring systems to support sustainable coaching and achievement improvement